COGNITIVE PROCESSING AND MEMORY TECHNIQUES IN CONSECUTIVE INTERPRETATION - Abduganiyeva, Djamila; Hodjaev, Malik (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This study investigates the psychophysiological characteristics and memory utilization in professional translators specializing in consecutive interpretation. Utilizing a comprehensive questionnaire, the study gathered data from practicing translators to understand how mechanical, logical, and imaginative memory strategies impact their translation performance, particularly focusing on spoken information retention over extended periods. Results indicate a strong preference for logical memorization due to its effectiveness in structuring and understanding complex information. However, imaginative memorization also plays a crucial role in scenarios requiring dynamic translation solutions. These findings suggest that training programs should emphasize versatile memory strategies to enhance translation accuracy and efficiency.